GIS-material for the archaeological project: Planned golf course in Hydinge and Päpplinge - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned construction of a golf course in Hydinge and Päpplinge, Sya parish, Mjölby municipality, the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a stage 1 survey during September-October 2004. Several different archaeological sites were concerned; stone settings, stone fences, prehistoric settlements and the medieval site of Hydinge village. The conclusion of the survey was that the development area constitutes a continuous and complex cultural environment with a high amount of visible remains of prehistoric and historical activities. In case the sites are affected by development, UV Öst suggests further archaeological measures to be taken.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the survey was mainly to get to know of all marked and registered archaeological remains that might be affected by the golf course and its building. In addition to this, possible prehistoric settlement locations were delimited, as well as the probable extent of the nearby burial grounds.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har utfört en arkeologisk utredning, etapp 1, inom Hydinge och Päpplinge, Sya socken, Mjölby kommun. Utredningen föranleddes av en planerad golfbana och fältarbete skedde under september-oktober 2004. Ett flertal olika fornlämningslokaler berördes; stensättningar, stensträngar, förhistoriska boplatser samt Hydinge gamla bytomt. Den arkeologiska utredningen konstaterade att exploateringsytan utgör en sammanhållen, komplex kulturmiljö med stort inslag av synliga lämningar av förhistoriska och historiska aktiviteter. I de fall platserna berörs av de planerade markingreppen föreslås fortsatta arkeologiska åtgärder.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med utredningen var i första hand att få kännedom om samtliga synliga registrerade fornlämningar som eventuellt kommer att beröras av golfbanan och dess byggnader. Utöver detta avgränsades lämpliga förhistoriska boplatslägen och den sannolika utbredningen av kringliggande gravfält.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Planerad golfbana inom Hydinge och Päpplinge
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive